Perspectives of local diclofenacol 1% liniment application in joint diseases - R M Balabanova; О Н Egorova; Т П Grishaeva; Н Е Lopatina; Г М Tarasova; A O Pchelintseva; Т П Fedina (Научно-практическая ревматология)
Objective. To assess efficacy and safety diclofenacol 1% liniment application in comparison with diclo- ran plus. Material and methods. An open controlled 2-weeks trial of diclofenacol 1% liniment on 30 pts with active joint syndrome (group 1) compared with dicloran plus 1% gel on 20 pts (group II). Pts age ranged from 16 to 79 years, mean disease duration was 8,2 1,5 years. Most pts had II activity degree. Results. Diclofenacol 1% liniment applications decreased pain at rest and at movement and circle of aim joints. In pts with RA effect was more prominent. Dicloran plus provided equivalent results. Local effect of diclofenacol appeared in average after 31,5 min. (from 10 to 73 min) and lasted during 118,3 min (from 50 to 240 min.). Diclofenacol allowed to decrease dose of oral NSAIDs in 43,3% of pts and dicloran - in 40% of pts. Diclofenacol safety was good without local and systemic adverse events. Conclusion. Diclofenacol 1% liniment manufactured by Hiperion S.A. (Rumania) can be recommended for wide administration in treatment of joint diseases particularly in pts with concomitant gastrointestinal diseases and hypertension.